2004
DOI: 10.1080/00288233.2004.9513596
|View full text |Cite
|
Sign up to set email alerts
|

The effect of litter size and sward height on ewe and lamb performance

Abstract: This study compared ewe and lamb performance in twin-and triplet-bearing/rearing ewes offered varying sward heights from day 64 (P64) of pregnancy until weaning at day 87 (L87) of lactation. Ninety-six twin-and 90 triplet-bearing Romney ewes were randomly assigned on P64 to four replicated sward height treatments (2, 4, 6, and 8 cm sward height). Within 24-36 h of parturition (L1) the ewes were reassigned to two (4 and 8 cm) replicated sward heights until weaning at L87. Ewes grazing the 2 cm sward height duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 21 publications
(25 reference statements)
6
78
2
1
Order By: Relevance
“…This was possibly due to the fact that in the multiparous group there was a greater number of goats that gave birth to triplets of kids in comparison to the primiparous group. A positive relationship between plasma NEFA and litter size was observed in ewes and goats (Morris and Kenyon, 2004;Laporte-Broux et al, 2011). In the present study, plasma NEFA concentration and litter size were positively correlated on the day of parturition.…”
Section: Plasma Metabolitessupporting
confidence: 66%
“…This was possibly due to the fact that in the multiparous group there was a greater number of goats that gave birth to triplets of kids in comparison to the primiparous group. A positive relationship between plasma NEFA and litter size was observed in ewes and goats (Morris and Kenyon, 2004;Laporte-Broux et al, 2011). In the present study, plasma NEFA concentration and litter size were positively correlated on the day of parturition.…”
Section: Plasma Metabolitessupporting
confidence: 66%
“…interestingly, there was a tendency for higher NEFA and β-hydroxybutyrate concentrations in mid to late pregnancy in the ad lib ewes compared to their Maintenance fed counterparts. Higher concentrations of these metabolites are observed under conditions of less than optimal nutrition (Morris & Kenyon 2004). However, given the relatively poor body condition scores, a subjective measure of level of adiposity, of the Maintenance fed ewes in late pregnancy it is possible that they had few body reserves to utilise, explaining the lower NEFa and β-hydroxybutyrate concentrations observed in this group.…”
Section: Discussionmentioning
confidence: 83%
“…The "Ad lib" nutritional regimen aim was to provide ad lib grazing conditions. Morris & Kenyon (2004) have previously shown that ewe intakes do not differ above a minimum cover of approximately 1200 kg DM/ha. Therefore, from P21 until P140, the four treatment groups included; large-ad lib (n = 151), large-Maintenance (n = 153), Small-ad lib (n = 155) and Small-Maintenance (n = 153), all of which contained singleton-and twin-bearing ewes.…”
Section: Experimental Designmentioning
confidence: 95%
See 1 more Smart Citation
“…The effects of differing herbage or concentrate feeding levels in mid and late pregnancy on triplet-bearing ewes and their offspring's performance has been examined in several studies (Everts 1990;Kleemann et al 1993;Hinch et al 1996;Morris & Kenyon 2004;Kenyon et al 2005Kenyon et al , 2010aKenyon et al , 2010bEverett-Hincks et al 2005;Corner et al 2008, Corner et al 2010Kerslake 2009Kerslake , 2010. Under pasture-based conditions, under-nutrition in mid to late pregnancy can result in reduced ewe liveweight, ewe body condition and lamb liveweight (Morris & Kenyon 2004;Corner et al 2008), poorer ewe and lamb behaviour post-birth (Everett-Hincks et al 2005;Corner et al 2010) and reduced indices of colostrum uptake .…”
Section: Introductionmentioning
confidence: 99%